2023
DOI: 10.3390/su152014798
|View full text |Cite
|
Sign up to set email alerts
|

A Spatial Analysis of Urban Streets under Deep Learning Based on Street View Imagery: Quantifying Perceptual and Elemental Perceptual Relationships

Haozun Sun,
Hong Xu,
Hao He
et al.

Abstract: Measuring the human perception of urban street space and exploring the street space elements that influence this perception have always interested geographic information and urban planning fields. However, most traditional efforts to investigate urban street perception are based on manual, usually time-consuming, inefficient, and subjective judgments. This shortcoming has a crucial impact on large-scale street spatial analyses. Fortunately, in recent years, deep learning models have gained robust element extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…This approach allowed for a nuanced understanding of the streetscape, delineating different elements within the urban environment through sophisticated feature extraction and segmentation. The use of the PSPNet model in this study ensured the use of a robust and efficient methodology for analyzing and categorizing streetscape features at the granular level [36]. This enabled our study to provide detailed analysis and fine-grained categorization of street view images, providing reliable data support for the analysis.…”
Section: Streetscape Measurements and Comparative Experimental Designmentioning
confidence: 99%
“…This approach allowed for a nuanced understanding of the streetscape, delineating different elements within the urban environment through sophisticated feature extraction and segmentation. The use of the PSPNet model in this study ensured the use of a robust and efficient methodology for analyzing and categorizing streetscape features at the granular level [36]. This enabled our study to provide detailed analysis and fine-grained categorization of street view images, providing reliable data support for the analysis.…”
Section: Streetscape Measurements and Comparative Experimental Designmentioning
confidence: 99%
“…Semantic segmentation refers to dividing and parsing images into several areas linked with semantic categories [132]. PSPNet has become a commonly used approach in emerging urban studies to extract street canyon characteristics [133][134][135] and has shown state-of-the-art performance on the ADE20K database, achieving an accuracy of over 80% [133,136].…”
Section: Independent Variables Svi Data Collectionmentioning
confidence: 99%
“…Semantic segmentation refers to dividing and parsing images into several areas linked with semantic categories (Guo et al, 2018). The PSPNet has become a commonly used approach by emerging urban studies to extract street canyon characteristics (Zhao et al, 2017;Yuan, Wang and Xu, 2022;Sun et al, 2023) and shown state-of-the-art performance on the ADE20K database, achieving an accuracy of over 80% (Zhao et al, 2017;Zhou et al, 2019).…”
Section: Semantic Segmentationmentioning
confidence: 99%